A digestive tract expressing α‐amylase influences the adult lifespan of Pteromalus puparum revealed through RNAi and rescue analyses. Issue 12 (31st May 2019) - Wang, Beibei; Yang, Yi; Liu, Mingming; Yang, Lei; Stanley, David W; Fang, Qi; Ye, Gongyin
Abstract: BACKGROUND: Midgut and salivary gland α‐amylases are digestive enzymes required for the development of insects and have been investigated in some insect species. However, α‐amylases in the endoparasitioid wasps have not been reported. Pteromalus puparum (Hymenoptera: Pteromalidae) is a dominant endoparasitioid wasp that parasitizes many butterfly species, including the Brassicaceae pest Pieris rapae (Lepidoptera: Pieridae). Here, we studied the characteristics and functions of three α‐amylases in P. puparum . RESULTS: We cloned three genes encoding α‐amylases in P. puparum, PpAmy1, PpAmy2 and PpAmy3 . The full length of the PpAmy1 cDNA is 1872 bp, encoding 496 amino acids, the PpAmy2 cDNA is 1863 bp long, encoding 518 amino acids, and PpAmy3 cDNA consists of 1802 bp encoding 521 amino acids. PpAmys are highly similar in amino acid sequences, but they have separate tissue distributions. Phylogenetic results show that gene duplications may occur between PpAmy2 and PpAmy3 . PpAmy1 and PpAmy3 are most highly expressed in the digestive tract and the venom apparatus, respectively, while PpAmy2 is broadly expressed in all tissues. We report that PpAmy1 acts in the digestive tract, where it influences lifespan as demonstrated using RNAi and α‐amylase rescue analyses, and there is no significant difference in longevity when PpAmy2 and PpAmy3 are knocked down. CONCLUSION: PpAmys probably have roles in carbohydrate metabolism of P. puparum and its host/parasitoid relationships. The characterization and functional study of PpAmys lays the foundation for the protection and utilization of parasitoid resources, and the biological control of agricultural pests. © 2019 Society of Chemical Industry Abstract : Identification and functional studies of three PpAmys were performed in Pteromalus puparum . PpAmy1, a digestive tract specific amylase, influences the adult life span of Pteromalus puparum . PpAmy3 was present in female venom.